MindFluctuations: Poetic, Aesthetic and Technical Considerations of a Dance Spectacle Exploring Neural Connections - Tania Fraga (TecnoLógicas, 2018)
In this era of co-evolution of humans and computers, we are witnessing a lot of fear that humanity will lose control and autonomy. This is a possibility. Another is the development of symbiotic systems among men and machines. To accomplish this goal, it is necessary to research ways to apply some key concepts that have a catalytic effect over such ideas. In the discussion of this hypothesis through the case study of the spectacle MindFluctuations—an experimental artwork exploring neural connections—we are looking for ways to develop them from conception to realization. The discussion also establishes a process of reflection on the design, development and production of this dance spectacle. This artwork uses a customized Java application, NumericVariations, to explore the quoted neural connections for spectacles, performances and site-specific installations. Its approach was made possible by recent neuroscience research and the development of a Brain Computer Interface (BCI) integrated with a virtual reality framework, which enable an experimental interactive virtual reality artwork to emerge. A neural helmet connected to the computer and entwined with mathematical procedures enabled a symbiosis of humans with computers.